INOVASI PENGELOLAAN KEHANDALAN WAKTU PERJALANAN (TRAVEL TIME RELIABILITY) - Noni Paisah (Asian Journal of Innovation and Entrepreneurship, 2014)
Time management is an important way to support the activities of individuals every day. Disorders of the trip cause variety of problems that might impact on the delay in achieving  performance and productivity optimal. To that end, each individual since the beginning to need  adoption of the  management methods innovation to implement the travel time reliability. This method has real value to help the use of a more appropriate time to reach the destination. Keywords: innovation, management, travel time reliability